1978
DOI: 10.1098/rspb.1978.0037
|View full text |Cite
|
Sign up to set email alerts
|

The photoreceptors and pigment epithelium of the larvalXenopusretina: morphogenesis and outer segment renewal

Abstract: Light microscopic autoradiography and electron microscopy were used to examine outer segment renewal and the development of photoreceptors and pigment epithelium in the larval Xenopus retina. Following the injection of [ 3 H]-leucine at stages 37/38–40 (when outer segments first develop) or 53–54 (when rod outer segments (r. o. s.) attain adult length), a band of label accumulated at the base of r. o. s. and was displaced sclerally with time, whereas label was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…How has electron microscopy of the base of the OS convincingly shown plasma membrane evaginations (4,7,8) in some studies and vesicles apparently enclosed by plasma membrane in others (5,12)? We have shown that the method of specimen preparation is key to preservation of the IS:OS interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How has electron microscopy of the base of the OS convincingly shown plasma membrane evaginations (4,7,8) in some studies and vesicles apparently enclosed by plasma membrane in others (5,12)? We have shown that the method of specimen preparation is key to preservation of the IS:OS interface.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the fusion model proposes that discs originate from rhodopsincontaining vesicles, which undergo homotypic fusion to form new discs (5, 6). Conventional electron microscopic (EM) analyses of chemically fixed specimens have clearly shown discs open to the extracellular space at the base of the OS, supporting the evagination model (4,7,8). Furthermore, studies in amphibians have demonstrated that membrane impermeant dyes can stain discs at the base of the rod OS, indicating they are not enclosed by plasma membrane (9, 10).…”
mentioning
confidence: 99%
“…The only OS sites that have been identified as growing fronts are the small number of incomplete basal lamellae, which expand by growing away from the cilium and are therefore best considered to be evaginations (Kinney and Fisher, 1978b;Anderson et al, 1978) rather than invaginations, as they were originally described (Sj6strand, 1961). Because such partially formed membrane outfoldings are consistently found at the extreme base of rod and cone OS and have not been described at other OS levels, I suggest they be termed"basal evaginations" (BE).…”
mentioning
confidence: 99%
“…In COS, as in ROS, newly synthesized membrane is apparently added by sclerad flow of the ciliary membrane at the OS base (Kinney and Fisher, 1978b;Holtzman and Mercurio, 1980;Papermaster and Schneider, 1982) and packets of membranes are discarded from the OS tip, but the intervening processes by which membrane is incorporated into the COS and travels from the base to the tip are not well understood. It is generally assumed (Young, 1976;Bok, 1985;Anderson et al, 1986;Roof, 1986) that COS exhibit no localLzation of autoradiographic labeling because molecules quickly diffuse throughout their fluid and topologically continuous membrane system, but the rate of longitudinal diffusion within COS membranes is not certain (of.…”
mentioning
confidence: 99%
“…However, these results are also consistent with alternative explanations, e.g., comigration or fusion of radiolabeled RIS-derived membranes containing newly synthesized, nonglycosylated opsin with unlabeled, previously formed ROS membranes during the isolation procedures. In this regard, electron microscopic and immunocytochemical studies have revealed the presence of opsin-containing vesicles in the periciliary region of the RIS cytoplasm, proximal to the ROS (7,29,47,48). In contrast, biochemical and light microscopic autoradiographic evidence from the study using Rana retinas (12) demonstrated that TM-mediated inhibition of opsin glycosylation resulted in a lack of assembly of opsin into new ROS membranes.…”
mentioning
confidence: 99%